Atrial fibrillation management: evaluating rate vs rhythm control. (2nd June 2016) - Nguyen, Tuan; Jolly, Umjeet; Sidhu, Kiran; Yee, Raymond; Leong-Sit, Peter
ABSTRACT: Atrial fibrillation (AF) is an increasing global issue leading to increased hospitalizations, adverse health related events and mortality. This review focuses on the management of atrial fibrillation, in particular in the past decade, comparing two major strategies, rate or rhythm control. We evaluate the evidence for each strategy, pharmacological options and the increasing utilization of invasive techniques, in particular catheter ablation and use of implantable cardiac pacing devices. Pharmacological comparative trials evaluating both strategies have shown rate control being non-inferior to rhythm control for clinical outcomes of mortality and other cardiovascular events (including stroke). Catheter ablation techniques, involving radiofrequency ablation and recently cryoablation, have shown promising results in particular with paroxysmal AF. However, persistent AF provides ongoing challenges and will be a particular focus of continued research.